Development of clean up protocol for sensitive DNA colorimetric assays - Kwek, Tian Chen (Nanyang Technological University, 2020)
An analytical Deoxyribo Nucleic Acid (DNA) colorimetric assay was done to find out how the detection limit are impinged in the presence of Bovine Serum albumin (BSA) in solution. DNA is known to be used as potential biomarkers for diagnosis of major diseases, such as cancer and heart diseases. However, the presence of interferents such as BSA affect the sensitivity of such biomarkers. While there are many detection techniques for DNA, there are often expensive, complex and require trained personnel. Thus, in this study, we made use of the optical properties conjugated polymers (CPs) to clean up BSA to improve sensitivity. In addition, CPs is used to detect DNA because of DNA’s fluorescence quenching abilities. The binding of DNA to cationic conjugated polymer through electrostatic interactions and docking of BSA to anionic polythiophene has been reported earlier. Two readily available conjugated polymers namely cationic polythiophene-1 (PT1) and anionic polythiophene-4(PT4) were used to demonstrate the fluorescence quenching after adding the biomolecules. Each polymer was added to react individually with DNA solutions, BSA solutions and a mixture of DNA and BSA solutions, respectively. Several parameters were varied, including volume, concentration of PTs and the different buffers for optimization. The absorbance and fluorescence spectra of the resulting solutions were measured using UV-Visible and fluorescence spectroscopy, respectively.